تحضير تشخيص والفعالية البيولوجية لجسيمات أكسيد الزنكZnO النانوية المفعل بTMSEDTA - صغيري, أسماء; مسعي عون, عفاف (universty of elouedجامعة الوادي, 2020)
"تم في هذه الدراسة تسليط الضوء على تحضير، تشخيص وتقدير الفاعلية البيولوجية لجسيمات أكسيد الزنك ZnO النانوية المصنعة بطريقة الترسيب الكيميائية والمفعلة بـ N-(trimethoxysilylpropyl) ZnO@TMSEDTA ethylenediamine triacetic acid ، ثم تشخيصها باستخدام تقنية حيود الاشعة السينية والاشعة تحت الحمراء بتحويل فوريه، أعطت قياسات ابعاد جسيمات اكسيد الزنك النانوية متوسط بعد حبيبي يقدر بـ 12.77 نانومتر وذو بنية بلورية سداسية من نوع Wurtzite، كما اثبتت نتائج الاشعة تحت الحمراء نجاح عملية التفعيل. أعطت نتائج الفاعلية المضادة للبكتيريا قيم تثبيطية متفاوتة بين المتوسطة والضعيفة جدا ضد ثلاث أنواع من السلالات البكتيرية الممرضة Escherichia coli ,Citrobacter sp وStaphylococcus epidermidis. ""The present study focuses on the synthesis ,characterization and the evaluation of the antimicrobial activities of zinc oxide nanoparticles and functionalized zinc oxide nanoparticles with N-(trimethoxysilylpropyl) ethylenediamine triacetic acid ZnO@TMSEDTA , ZnO NPs prepared using precipitation method at low temperature. they were characterized by diffraction of X rays and Fourier transform infrared spectra (FTIR). which all concur with the successful synthesis of ZnO nanoparticles with average size of 12.77 nm as well as the efficiency of TMSEDTA grafting on ZnO. The obtained results of the anti-bacterial activities which were effected by well diffusion method confirmed a varied inhibition values (medium to weak) between the different bacterial strains studies such as Escherichia coli , Citrobacter sp and Staphylococcus epidermidis. "
preparation characterization and bioactivity of functionalized Zino oxide nanoparticle by TMSEDTA
مذكرة تخرج ماستر كيمياء
Keywords: أكسيد الزنك، تفعيل، ZnO@TMSEDTA، تحضير، تشخيص، الفاعلية البيولوجية.; Zinc Oxide, ZnO@TMSEDTA, Synthesis, Antimicrobial activities, Functionalization, Characterization